The natural history of a Neapolitan miracle - De Ceglia, Francesco Paolo, author.
1 online resource (xii, 424 pages)
Keywords: "This book examines the Naples' patron saint, Gennaro, the history of his blood relic and the mystery of its periodical liquefaction. Three times a year Neapolitans gather to witness the recurring phenomenon of the liquefaction of Saint Gennaro's blood. From the seventeenth century to the present, crowds have prayed to the city's patron for protection from fires, earthquakes, plagues, droughts, and the fury of Mt. Vesuvius. In the "miraculous" moment of transposition from solid to liquid, the faithful seek respite from the ills of the world in the saintly blood, a visual reminder of the blood of Christ spilled for their salvation. In Naples, the periodical liquefaction of Saint Gennaro's blood is not officially recognized as miraculous by the Catholic Church, which now more cautiously refers to it as a prodigy. Nevertheless, for centuries, this phenomenon has been called "a miracle" in liturgical texts approved by the ecclesiastical authority and in the words of bishops, cardinals, popes and saints. However not everyone agreed. This volume follows the efforts of theologians, alchemists, charlatans and scientists who through the centuries have tried to answer questions such as: Is the liquefaction of Saint Gennaro's blood really a miracle? If not, how is it possible to explain a phenomenon that only occurs on dates liturgically relevant to the saint? The Natural History of a Neapolitan Miracle will be of great value to those interested in Religious Studies, Italian Studies, Medieval and Early Modern Studies, as well as the History of Science, Anthropology and Ethnography"--